Message in a bottle - Costner, Kevin; Wright, Robin 1966-.; Mandoki, Luis.; Sparks, Nicholas; De Novi, Denise; Wilson, Jim.; DiPego, Gerald; Warner Bros.; Tig Productions; Bel-Air Entertainment (Firm).; Di Novi Pictures (Firm).; Warner Home Video (Firm). ([S.l.] Warner Home Video (Phils.), 1999)
A reporter traces a lonely widower who wrote a heart-felt message, put it in a bottle, and threw it in the sea.
Based on the novel by Nicholas Sparks.
Originally produced as motion picture in 1999.
Editor, Steven Weisberg ; music, Gabriel Yared.
Kevin Costner, Robin Wright Penn, Paul Newman.
VHS ; Dolby digital.
Closed-captioned for hearing impaired.
Keywords: Man-woman relationships -- Drama; Widowers -- Drama; Romance films; Feature films